2019
DOI: 10.1186/s40425-019-0677-y
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human phase 1 study of IT1208, a defucosylated humanized anti-CD4 depleting antibody, in patients with advanced solid tumors

Abstract: Background Transient CD4 + T cell depletion led to the proliferation of tumor-specific CD8 + T cells in the draining lymph node and increased infiltration of PD-1 + CD8 + T cells into the tumor, which resulted in strong anti-tumor effects in tumor-bearing mice. This is a first-in-human study of IT1208, a defucosylated humanized anti-CD4 monoclonal antibody, engineered to exert potent antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Interestingly, TYROBP and C1QB were both correlated with immune infiltration levels, suggesting a potential key role in prognosis of GC patients. These factors have previously been positively associated with three predictive biomarkers for immunotherapy in GC, including PD-L1 expression (42,43), CD8 + T cells infiltration (44) and EBV status (45,46). Previous studies have shown that TYROBP, also known as DAP12, is overexpressed and related to tumor progression in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TYROBP and C1QB were both correlated with immune infiltration levels, suggesting a potential key role in prognosis of GC patients. These factors have previously been positively associated with three predictive biomarkers for immunotherapy in GC, including PD-L1 expression (42,43), CD8 + T cells infiltration (44) and EBV status (45,46). Previous studies have shown that TYROBP, also known as DAP12, is overexpressed and related to tumor progression in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For some patients with distant metastases, palliative local treatments are chosen to control and delay disease progression [15]. With the enhanced study of the immune system, immunotherapy has emerged as very promising method to treat sarcomas after surgery and chemotherapy [16].…”
Section: Introductionmentioning
confidence: 99%
“…For some patients with distant metastases, palliative local treatments are chosen to control and delay disease progression [ 15 ]. With the enhanced study of the immune system, immunotherapy has emerged as very promising method to treat sarcomas after surgery and chemotherapy [ 16 ]. Researchers have adopted various immunotherapy strategies for different types of immune deficiency, but the main treatment obstacles are identifying the specific target antigen and dealing with the severe adverse effects of the selected treatment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For some patients with distant metastases, palliative local treatments are chosen to control and delay disease progression [15]. With the enhanced study of the immune system, immunotherapy has emerged as very promising method to treat sarcomas after surgery and chemotherapy [16]. Researchers have adopted various immunotherapy strategies for different types of immune de ciency, but the main treatment obstacles are identifying the speci c target antigen and dealing with the severe adverse effects of the selected treatment [17].…”
Section: Introductionmentioning
confidence: 99%